Students’ difficulties pronouncing vocabulary mastery of second semester in english department at university students - Firmansyah, Moh; Purwaningsih, Dewi Ismu; Rofiqoh, Rofiqoh; Selviani, Selviani (Universitas Madako Tolitoli, 2023)
The research objective is to discover the students' vocabulary mastery difficulties. The method applied was descriptive qualitative. The sample of this research was class B students in 2 semesters at Madako University, and the data were obtained from interviews. The researcher took five students as a sample. The result of this research showed that students have difficulties in pronouncing the vocabulary. The students lack the self-confidence to pronounce the vocabulary because they fear producing it incorrectly. They feel too lazy to learn a new vocabulary, and the students have difficulties pronouncing the new words because the written and pronunciation are different. This research was conducted on students of the second semester class B in the English Department at Madako University, who have enough self-confidence in pronouncing the vocabulary because they are afraid to produce it incorrectly, they also feel lazy to learn new vocabulary because they did not know how to pronounce words correctly, and the written words and the pronunciation were totally different. Doing more practice and always being guided by the lecturer when practicing will help them solve their difficulties in mastering vocabulary.